Pelatihan penyusunan perangkat pembelajaran berbasis TPACK menggunakan kurikulum Prototipe - Luvy Sylviana Zanthy; Anik Yuliani; Eva Dwi Minarti (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2022)
This community service aims to introduce a prototype curriculum and improve the ability of mathematics teachers in West Bandung Regency in preparing TPACK-based learning tools. This activity is in the form of simple training, namely following the examples provided which consist of two sessions, namely: 1) Introduction to prototype curriculum, and 2) Training on the development of TPACK-based learning tools, which consists of: a) Training on the preparation of learning tools using the Liveworksheet application and b) Training on the preparation of learning tools using the Anyflip application. The resulting product is a TPACK-based learning device for mathematics subjects in elementary schools. From the results of observations and interviews with participants, it is known that 70 percent of participants have been able to compose simple TPACK learning tools, besides that the four indicators are: 1) participants' motivation in participating in activities; 2) new knowledge about prototype curriculum; 3) knowing new knowledge and skills about TPACK-based learning, and 4) the number of participants who are able to compose learning has been fulfilled, it can be said that this activity can improve the abilities and skills of mathematics teachers in West Bandung Regency in preparing TPACK-based learning tools using curriculum prototypes